Prevalence and correlates of personality disorders in males with alcohol dependence syndrome undergoing inpatient treatment in a tertiary care hospital in South India - Aravindan Balachandran; Parthasarathy Ramamurthy; Pradeep Thilakan (Indian Journal of Psychiatry, 2023)
Background: Globally, about half the patients with alcohol dependence syndrome have a comorbid personality disorder (PD). Indian studies that have explored this are sparse. Objectives: The present study was conducted to estimate the prevalence of personality disorders in individuals with alcohol dependence syndrome undergoing inpatient treatment and to determine the sociodemographic and clinical correlates of PDs in these patients. Methods: This cross-sectional observational study was conducted among the inpatients of the psychiatry department in a tertiary care teaching hospital. Adult male patients with DSM-IV TR diagnosis of alcohol dependence were evaluated for the presence of PDs using Structured Clinical Interview for DSM IV Axis II Personality disorders. The severity of alcohol dependence was assessed using the Severity of Alcohol Dependence Questionnaire. Results: One hundred male inpatients with alcohol dependence syndrome were recruited. Of them, 48 (48%) participants had at least one PD with a 95% confidence interval of 0.38-0.58. Antisocial and avoidant PDs were found in 26 (26%) and 13 (13%) patients, respectively. The mean age at first drink was lower in participants with PD when compared to those without any PD (18.13 ± 4.46 vs. 20.79 ± 4.61 years, respectively). Also, the amount of alcohol consumption per day was significantly higher in those with PD when compared to those without any PD (15.9 ± 6.81 vs. 13.17 ± 4.34 units per day). Conclusion: About half of males with alcohol dependence syndrome undergoing inpatient treatment had at least one PD. Antisocial and avoidant PDs were the most common PDs in this population. Individuals with comorbid PD had a lower age at first drink and higher daily alcohol consumption.